Intelligent accounting digital maturity model for small and medium-sized accounting firms - Kortesalmi, Heli (Emerald, 2025)
Purpose This paper aims to present a digital maturity model for intelligent automation, specifically designed for small and medium-sized accounting firms. Intelligent automation facilitates the execution of complex accounting tasks, leading to notable improvements in operational efficiency, client satisfaction and employee engagement. Despite these benefits, smaller firms often face challenges in adopting automation due to constrained resources and limited expertise. The proposed maturity model supports firms in evaluating their current level of digital advancement and provides a structured pathway for progressing towards more sophisticated automation capabilities. Design/methodology/approach The model was developed following a design science-based procedure model. The development began with a systematic literature review. Subsequently, the model was refined on the basis of feedback from 15 expert interviews conducted in Finland. Finally, it was evaluated in three accounting firms. Findings The final digital maturity model encompasses 11 dimensions. Four of the dimensions are typical for digital maturity models: technology, processes, vision and leadership and data and cybersecurity. The remaining dimensions are tailored to accounting firms: role of the accountant, sales to cash, purchase to pay, payments, general ledger, reporting and customer communication and payroll. Each dimension is scaled across five levels: non-existent, initial, proficient, advanced and continuous improvement. Originality/value The developed digital maturity model advances the limited academic literature on digital maturity models in accounting, demonstrates the application of intelligent automation within accounting firms and serves as a practical tool to support these firms in their automation efforts.
Keywords: SME; IPA; Accounting; Artificial intelligence; Design science; AI; DMA; Digital maturity model; Intelligent accounting; Intelligent process automation; Automated accounting; fi=Laskentatoimi|en=Accounting|